2020
DOI: 10.3389/fpls.2020.00135
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones Decrease Leaf Angle in Response to Nutrient Deficiencies in Rice

Abstract: Strigolactones (SLs) are a class of plant hormones that are synthesized from b-carotene through sequential reactions catalyzed by DWARF (D) 27, D17, D10, and OsMORE AXILLARY GROWTH (MAX) 1 in rice (Oryza sativa L.). In rice, endogenous SL levels increase in response to deficiency of nitrogen, phosphate, or sulfate (−N, −P, or −S). Rice SL mutants show increased lamina joint (LJ) angle as well as dwarfism, delayed leaf senescence, and enhanced shoot branching. The LJ angle is an important trait that determines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 65 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…For instance, Arabidopsis, rice, and pea SL‐deficient and ‐insensitive mutants showed a higher degree of shoot branching/tillering than the wild type (Gomez‐Roldan et al ., 2008; Umehara et al ., 2008). Furthermore, SLs are involved in many other shoot‐related developmental processes such as regulation of rice tiller angle by attenuating shoot gravitropism (Sang et al ., 2014), promotion of shoot secondary growth, elongation of internodes (Agusti et al ., 2011; de Saint et al ., 2013), inhibition of hypocotyl and mesocotyl growth (Hu et al ., 2010; Tsuchiya et al ., 2010; Hu et al ., 2014; Jia et al ., 2014; Sun et al ., 2018; Wang et al ., 2020c), induction of leaf senescence (Snowden et al ., 2005; Yamada et al ., 2014) and decreasing the rice leaf angle in response to nutrient deficiencies (Sun et al ., 2014; Shindo et al ., 2020). They also play key roles in determining root architecture.…”
Section: Sl Functions and Biosynthesismentioning
confidence: 99%
“…For instance, Arabidopsis, rice, and pea SL‐deficient and ‐insensitive mutants showed a higher degree of shoot branching/tillering than the wild type (Gomez‐Roldan et al ., 2008; Umehara et al ., 2008). Furthermore, SLs are involved in many other shoot‐related developmental processes such as regulation of rice tiller angle by attenuating shoot gravitropism (Sang et al ., 2014), promotion of shoot secondary growth, elongation of internodes (Agusti et al ., 2011; de Saint et al ., 2013), inhibition of hypocotyl and mesocotyl growth (Hu et al ., 2010; Tsuchiya et al ., 2010; Hu et al ., 2014; Jia et al ., 2014; Sun et al ., 2018; Wang et al ., 2020c), induction of leaf senescence (Snowden et al ., 2005; Yamada et al ., 2014) and decreasing the rice leaf angle in response to nutrient deficiencies (Sun et al ., 2014; Shindo et al ., 2020). They also play key roles in determining root architecture.…”
Section: Sl Functions and Biosynthesismentioning
confidence: 99%
“…SLs negatively regulate leaf inclination at seedling stage [ 77 ]. Interestingly, recent report showed that SLs also mediated leaf inclination in response to nutrient deficiencies in rice [ 78 ]. Similar to SLs, JA also showed a negative role in leaf inclination.…”
Section: Other Phytohormones Involved In Regulation Of Lamina Joinmentioning
confidence: 99%
“…Strigolactones (SLs) are a family of plant hormones derived from β‐carotene that have diverse functions in plants (Bouwmeester et al, 2021 ; Machin et al, 2020 ; Waters et al, 2017 ). SLs regulate axillary bud outgrowth (tillering), stem elongation, auxin transport, root elongation, leaf shape, leaf angle, leaf senescence, cambial growth, susceptibility to pathogenic microbes and root‐knot nematodes, stomatal closure responses, and drought tolerance (Agusti et al, 2011 ; Bu et al, 2014 ; Gomez‐Roldan et al, 2008 ; Kalliola et al, 2020 ; Kapulnik et al, 2011 ; Lahari et al, 2019 ; Lauressergues et al, 2015 ; Li et al, 2017 , 2020 ; Marzec et al, 2016 ; Nasir et al, 2019 ; Ruyter‐Spira et al, 2011 ; Scaffidi et al, 2013 ; Shindo et al, 2020 ; Shinohara et al, 2013 ; Soundappan et al, 2015 ; Ueda & Kusaba, 2015 ; Umehara et al, 2008 ; Van Ha et al, 2014 ; Yamada et al, 2014 ). SLs are also exuded by roots into the rhizosphere, especially under nutrient‐poor conditions.…”
Section: Introductionmentioning
confidence: 99%